2003
DOI: 10.1523/jneurosci.23-12-05050.2003
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Neurotrophins and Schwann Cell-Derived Signals on Neuronal Survival/Growth and Synaptogenesis

Abstract: Recent studies have shown that the survival of mammalian motoneurons in vitro is promoted by neurotrophins (NTs) and cAMP. There is also evidence that neurotrophins enhance transmitter release. We thus investigated whether these agents also promote synaptogenesis. Cultured Xenopus spinal cord neurons were treated with a mixture of BDNF, glia-derived neurotrophic factor, NT-3, and NT-4, in addition to forskolin and IBMX or the cell-permeant form of cAMP, to elevate the cAMP level. The outgrowth and survival of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 66 publications
6
90
0
7
Order By: Relevance
“…In cultures con- taining embryonic Xenopus spinal neurons and muscle, neurotrophic factors and elevated cAMP induce a dramatic increase in neuron survival and neurite outgrowth (Peng et al, 2003). However, the number of nerve-muscle contacts that showed AChR clusters was greatly inhibited.…”
Section: Perisynaptic Schwann Cells In Neuromuscular Junction Developmentioning
confidence: 99%
See 1 more Smart Citation
“…In cultures con- taining embryonic Xenopus spinal neurons and muscle, neurotrophic factors and elevated cAMP induce a dramatic increase in neuron survival and neurite outgrowth (Peng et al, 2003). However, the number of nerve-muscle contacts that showed AChR clusters was greatly inhibited.…”
Section: Perisynaptic Schwann Cells In Neuromuscular Junction Developmentioning
confidence: 99%
“…However, the number of nerve-muscle contacts that showed AChR clusters was greatly inhibited. Interestingly, addition of medium conditioned by SCs or TGF-␤1 increased AChR clusters at neuron-muscle contacts (Peng et al, 2003;Feng and Ko, 2004). These findings suggested that Schwann cell-derived factors allow neurons to switch from a "growth phase" to a "synaptogenic phase."…”
Section: Perisynaptic Schwann Cells In Neuromuscular Junction Developmentioning
confidence: 99%
“…Notably, an interesting study showed recently that neurotrophins support survival and growth of cultured frog spinal cord neurons, but inhibit agrin synthesis and thus NMJ formation. However, soluble, as-yet unidentified Schwann-cell-derived factors override this inhibition and switch motoneurons to a synaptogenic state [16]. It will be interesting to see whether such a binary regulation of NMJ formation is implemented in vivo and whether a similar principle applies to synaptogenesis in the CNS.…”
Section: Trends In Neurosciencesmentioning
confidence: 99%
“…Owing to space limitations, the article focuses mainly on connections in the CNS. However, it should be noted that glial cells also appear to influence synaptogenesis in the peripheral nervous system (PNS) [14][15][16][17][18][19]). …”
mentioning
confidence: 99%
“…To investigate how Schwann cells promote synaptogenesis, we have shown previously that Schwann cell-conditioned medium (SC-CM) can increase the number of nerve-muscle contacts in Xenopus tissue culture (Peng et al, 2003). However, it has been unclear whether Schwann cells promote synaptic function at developing NMJs.…”
Section: Introductionmentioning
confidence: 99%